Croatian Old Dictionary Portal (CRODIP) - Boras, Damir (Array, 2005)
The Croatian Old Dictionary Portal (CRODIP) presents the diachronic vocabulary of the Croatian language, based on selected Croatian manuscripts and printed dictionaries from the late 16th to the 19th century, using today's most advanced technology. Since these dictionaries are multi-lingual ones (all of them include Latin, and some dictionaries also include Italian, German and Hungarian), by using the full text search, it is possible to explore the vocabularies of other languages as well. It comprises F. Vrančić's (1595), P. Loderecker's (1605), B. Kašić's (manuscript, 17th cent.), J. Habdelić’ s (1670), Della Bella's (1728 and 1782), and I. Belostenecz’ s (1740) printed dictionaries. The full text search includes options to retrieve information from the specific dictionary or from all of them. If all the dictionaries are selected, it is possible to search only by two languages, Croatian and Latin. Otherwise, if only the specific dictionary is selected, it is possible to perform advanced search with up to five languages. Experienced dictionary users can exploit the use of the specific characters and/or transcription. Furthermore, the dictionary entry context and link to the original image of the entry are also returned as the search result. CRODIP offers the possibility to the user to report errors in the dictionary entry. These errors relate only to those made during the digitalization process, and can be perceieved only by comapring the entry to its original image. Mistakes made by authors in the original dictionary are not corrected at all in order to keep the integrity of the original document, but some of the dictionaries contain the translation to the modern language and corrections of mistakes. The techical part of the project includes SQL server, client and server side scripting languages, as well as the relational database module. CRODIP is a major resource for scholars of the linguistics, literature, history and culture of above mentioned languages, defining and illustrating as it does every word found in the surviving records, so touching upon every facet of the 16th and 17th century's life and society. It is also a pioneer in the application of technology to Croatian old dictionaries. Our final goal is to make these dictionaries available for complex searches to any institution and researcher in the world and establish new principles of on-line presentation.